The Impact of Promoting Alternative Thinking Strategies (PATHS) on Loneliness in Primary School Children: Results From a Randomized Controlled Trial in England - Hennessey, Alexandra; Qualter, Pamela; Humphrey, Neil (Frontiers in Education, 2021)
Research suggests that loneliness during childhood is associated with poor well-being and mental ill-health. There is a growing social and educational imperative to explore how school-based interventions can support young children’s social development. The Promoting Alternative Thinking Strategies (PATHS) curriculum is a universal school intervention focused on social and emotional learning, and it has a significant evidence based supporting its positive impact on children’s social-emotional and mental health outcomes. Yet the impact on children’s reported loneliness has not been explored. This paper presents the first large scale analyses of the impact of PATHS on reducing children’s loneliness in England. A cluster randomized controlled trial (RCT) with two arms: intervention (PATHS—23 schools) and control (usual practice—22 schools) assessed the impact of PATHS on children’s loneliness from baseline to 2-year follow-up. Two-level (school, child) multi-nomial regression models were used to assess “intention-to-treat” effects, controlling for important demographic co-variates such as gender, age, free school meal eligibility, ethnicity, and special educational needs. These analyses revealed a significant positive effect of PATHS on children’s loneliness. Furthermore, sensitivity analyses, treating loneliness as a dichotomous variable and using different cut-offs for loneliness, revealed the positive effect of PATHS was maintained and, thus, robust. This is the first RCT to demonstrate that a school-based universal social-emotional learning intervention such as PATHS can reduce loneliness in children.